(untitled) (Research, Society and Development, 2023)
One way to increase the reproductive efficiency and genetic merit of a herd is by biotechnologies such as artificial insemination and in vitro fertilization, in which frozen semen is essential. Thus, the aim of this study was to compare the concentrations of glutathione and vitamin-C as antioxidant agents, with six ejaculates from six different bulls allocated to each group. Each ejaculate was exposed to four treatments (control/ 1.25mM/ 2.5mM/ 5.0mM) for both glutathione and vitamin C. After cryopreservation, tests were performed to assess seminal quality after thawing through hyposmotic tests, sperm longevity and giemsa/trypan blue. No groups of bulls were contrasted, only treatments within each group. For the glutathione group, there was no significant difference (P>0.05) between the results and the concentrations used, whereas in the vitamin-C group, the 5.0 mM concentration showed unfavorable results compared to the others, indicating damage to the acrosomal membrane, being contraindicated.